Digital Literacy Competence and Instructional Technology Proficiency Among Elementary School Educators : Implications for 21st-Century Teaching - Laggui, Regine; Gonzales, Alma (Azal Arts and Humanities, 2026)
Digital literacy competence and instructional technology proficiency have become essential components of effective 21st-century teaching practices in contemporary education. This study explored the digital literacy competence and instructional technology proficiency among elementary school educators in Santa Maria, Isabela. Anchored on the Technological Pedagogical Content Knowledge (TPACK) Framework and Constructivist Learning Theory, the study employed a descriptive qualitative research design to examine teachers’ digital experiences, instructional technology practices, classroom integration strategies, and challenges in technology-enhanced instruction. Participants included selected elementary school educators from public schools in Santa Maria, Isabela. Data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Braun and Clarke’s (2006) thematic analysis approach was utilized in analyzing the gathered data. Findings revealed that teachers utilize digital platforms, multimedia resources, online learning applications, and technology-assisted instructional strategies to improve learner engagement, classroom participation, and instructional delivery. Participants emphasized that digital literacy competence enhances classroom interaction, instructional creativity, communication efficiency, and access to learning resources. The findings further revealed that teachers continuously adapt to emerging educational technologies through self-directed learning, peer collaboration, and professional development initiatives. However, challenges such as unstable internet connectivity, limited technological resources, inadequate training opportunities, varying digital competencies, and workload demands significantly affect instructional technology integration. The study concludes that digital literacy competence and instructional technology proficiency significantly contribute to innovative and learner-centered teaching practices in elementary education. Strengthening technological infrastructure, continuous professional development, digital support systems, and institutional technology programs is recommended to improve instructional technology integration and 21st-century teaching practices among educators.